Feasibility Study of Using Energy Harvesting Systems in Terms of Energy production and Economic Evaluation for a Nanogrid Road Lighting System - Suntiti Yoomak; Atthapol Ngaopitakkul (My University, 2022)
This study investigated the feasibility of using a wind energy harvesting in a nano-grid road lighting system. A two-blade Savonius wind turbine was installed on a traffic island to generate electrical energy from vehicle movement. The wind flow velocity stemming from the movement of different vehicles and affecting the wind turbine was analysed by computational fluid dynamics method using ANSYS software. The economic feasibility of using various energy harvesting systems for solar, wind, and piezoelectric energy for a nano-grid road lighting system was evaluated. Further, the optimisation between different renewable energy sources and storage systems for the nano-grid road lighting system was performed using HOMER Pro software. The results showed that the electrical energy production using wind velocity from vehicle movement was feasible, although the wind velocity was unstable. An economic evaluation revealed that the use of piezoelectric energy systems was unfeasible owing to their high investment costs compared to their power generation. The behaviour of power generation from renewable energy and load consumption significantly affected the size of energy harvesting and storage systems. Therefore, the mismatch between solar energy and road lighting system consumption increased the size of solar and energy storage systems, leading to low economic feasibility. In contrast, the hybrid solar–wind system demonstrated great economic feasibility.
Keywords: Innovative Energy Harvesting Technologies; Energy Harvesting in Wireless Networks; Electric Vehicles and Infrastructure